Use of Comic Media in Science Learning in Elementary Schools - Mauludyah, Ida; Septinaningrum, Septinaningrum (Alifbata : Jurnal Pendidikan Dasar, 2023)
Comics are a type of graphic media in the form of stories that emphasize students' sense of sight in receiving information in the form of learning material presented by the teacher. The tendency of students not to be very interested in textbooks means that comics are starting to be used as a learning medium. This research aims to determine the use of comic media in science learning in elementary schools. The research method used in this research is a qualitative descriptive research method. Based on the object of study, this research is included in bibliographic research. Data collection was carried out by documenting all articles that had similar research to this research report. Based on this research, the results showed that comic media can be used as a science learning medium in elementary schools.